The Influence of the Home Owners' Loan Corporation on Housing Markets During the 1930s - Fishback, Price V.; Flores-Lagunes, Alfonso; Horrace, William C.; Kantor, Shawn; Treber, Jaret (Review of Financial Studies, 2011)
Problems with mortgage financing are widely considered to be a major cause of the recent financial meltdown. Several modern programs have been designed to mimic the Home Owners' Loan Corporation of the 1930s. The HOLC replaced the toxic assets on the balance sheets of financial institutions by buying troubled mortgages and then refinanced the mortgages to allow home owners to avoid losing their homes. We analyze the impact of the HOLC on the nonfarm rental and owned home markets after developing a new data set for over 2800 counties in the United States. In counties with fewer than 50,000 people, where financial markets were not as well developed as in larger cities, the HOLC's financial interventions helped stimulate the demand for owned housing more than it influenced the supply. In rental markets the HOLC appears to have contributed to an increase in the supply of rental housing that was likely associated the improvement of the balance sheets of lending institutions.